2014
DOI: 10.1371/journal.pone.0103679
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cross-Reactive, Immunodominant and HLA-Promiscuous Epitope of Mycobacterium tuberculosis-Specific Major Antigenic Protein PPE68

Abstract: PPE68 (Rv3873), a major antignic protein encoded by Mycobacteriun tuberculosis-specific genomic region of difference (RD)1, is a strong stimulator of peripheral blood mononuclear cells (PBMCs) obtained from tuberculosis patients and Mycobacterium bovis bacillus Calmette Guerin (BCG)-vaccianted healthy subjects in T helper (Th)1 cell assays, i.e. antigen-induced proliferation and interferon-gamma (IFN-γ) secretion. To confirm the antigen-specific recognition of PPE68 by T cells in IFN-γ assays, antigen-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Five of the 11 genomic pairs are contained in five loci: ESX-1 to ESX-5 encoding components of the type VII secretion system (Uplekar et al, 2011 ). Four of the five loci, except ESX-4, also harbor 11 proteins of the Proline Glutamate (PE), or Proline Proline Glutamate (PPE) family, several of which have been implicated in immune evasion (Akhter et al, 2012 ; Mustafa, 2014 ). The PE and PPE and Esx proteins whose genes are adjacent to each other in the genome of Mycobacterium tuberculosis interact to form pairs which appear to be essential for their secretion (Renshaw et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the 11 genomic pairs are contained in five loci: ESX-1 to ESX-5 encoding components of the type VII secretion system (Uplekar et al, 2011 ). Four of the five loci, except ESX-4, also harbor 11 proteins of the Proline Glutamate (PE), or Proline Proline Glutamate (PPE) family, several of which have been implicated in immune evasion (Akhter et al, 2012 ; Mustafa, 2014 ). The PE and PPE and Esx proteins whose genes are adjacent to each other in the genome of Mycobacterium tuberculosis interact to form pairs which appear to be essential for their secretion (Renshaw et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PE and PPE and Esx proteins whose genes are adjacent to each other in the genome of Mycobacterium tuberculosis interact to form pairs which appear to be essential for their secretion (Renshaw et al, 2005 ). The secretory proteins have been the focus of research aimed at development of TB vaccines and immunodiagnostic assays, because they are thought to have a potential to induce protective immunity and immune responses of diagnostic value (Ize and Palmer, 2006 ; Ganguly et al, 2008 ; Marongui et al, 2013 ; Mustafa, 2014 ). Studies have shown however, that some genes encoding for proteins of the Esx family, as well as PE/PPE do occur in pathogenic NTM like Mycobacterium kansasii Mycobacterium marinum, Mycobacterium szulgai, Mycobacterium gordonae, Mycobacterium gastri, Mycobacterium ulcerans, Mycobacterium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Promiscuous peptides for HLA class II were 24% (19/79) and none for HLA class I molecules. Interestingly, the presence of promiscuous peptides for HLA class II suggest that these peptides could have role in presentation of antigens for immune recognition and amplification of response against M.tb ( Table 3 and 4 ) [ 30 ]. Genetic studies on HLA class I and II alleles are associated with susceptibility to disease and the present study indicates their similarities/binding to M.tb virulent factors.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we generally focus on enhancing the Th1/IFN-g response for novel TB vaccines (Stephen-Victor et al, 2016). PE27 (Kim et al, 2016) and PPE68 (Rv3873) (Mustafa, 2014) can induce Th1 cell response in host, suggesting their TB vaccine potential. Deletion peptides assay indicates that aa 127-FFGINTIPIA-136 of PPE68 is the immunodominant and HLA-DR promiscuous core sequence.…”
Section: Additional Roles Of Pe/ppe Proteinmentioning
confidence: 99%
“…Deletion peptides assay indicates that aa 127-FFGINTIPIA-136 of PPE68 is the immunodominant and HLA-DR promiscuous core sequence. Intriguingly, the core sequence is conserved in all sequenced strains/species of MTB and MTB complex, and several other pathogenic mycobacterial species, including M. leprae and M. avium-intracellulare complex, indicating that the peptide aa 121-145 has potential to be a peptidebased vaccine candidate against TB and other mycobacterial infection (Mustafa, 2014).…”
Section: Additional Roles Of Pe/ppe Proteinmentioning
confidence: 99%